Emotional socialisation and burnout in medicine and the role of medical educators. Issue 4 (15th January 2019) - Laws, Elinor; Samuriwo, Ray; Webb, Katie; Bullock, Alison
Abstract : The authors highlight the importance of exploring the role that nurses and other healthcare professionals play in supporting medical students and doctors to develop their emotional competence.